TRANSFORMING ECONOMIES: NAVIGATING GLOBAL CHALLENGES IN THE DIGITAL ERA - Muhamad Rahman Bayumi; Dur Brutu; Ria Agustina; Rizal Alfit Jaya (Journal of Economics and Development, 2024)
The rapid digital transformation has significantly reshaped the global economy, introducing both opportunities and challenges. This study aims to analyze the impact of digital transformation on economic development, particularly in addressing contemporary global issues such as climate change, economic inequality, and post-pandemic recovery. Utilizing a qualitative approach, this research relies on secondary data analysis from scientific articles, global reports, and case studies of both developed and developing countries. The findings reveal that countries with high levels of technology adoption experience faster economic growth but face persistent digital divides. Digitalization is also identified as a catalyst for sustainable development, offering innovative solutions in sectors such as education, health, and e-commerce. However, addressing infrastructure gaps, digital literacy, and policy frameworks remains crucial. This study highlights the importance of inclusive and collaborative strategies to ensure that digital transformation supports resilience and sustainability in the global economy.